1993
DOI: 10.1007/bf00010766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high temperature on nodulation and nitrogen fixation by Phaseolus vulgaris L.

Abstract: Screening of Rhizobium leguminosarum bv. phaseoli strains showed some that were able to nodulate common beans (Phaseolus vulgaris L.) at high temperatures (35 and 38°C/8h/day). The nodulation ability was not related to the capability to grow or produce melanin-like pigment in culture media at high temperatures. However, nodules formed at high temperatures were ineffective and plants did not accumulate N in shoots. Two thermal shocks of 40°C/8 h/day at flowering time drastically decreased nitrogenase activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 25 publications
3
52
0
4
Order By: Relevance
“…Soil temperature affects many aspects of the N 2 fixation process, including nodulation (Barrios et al 1963;Purwantari et al 1995), nodule development (Piha and Munns 1987) and nodule activity (Meyer and Anderson 1959;Hungria and Franco 1993). Both extreme soil temperatures and drought inhibit all of these aspects (Serraj et al 1999;Aranjuelo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Soil temperature affects many aspects of the N 2 fixation process, including nodulation (Barrios et al 1963;Purwantari et al 1995), nodule development (Piha and Munns 1987) and nodule activity (Meyer and Anderson 1959;Hungria and Franco 1993). Both extreme soil temperatures and drought inhibit all of these aspects (Serraj et al 1999;Aranjuelo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in conformity with those obtained by many other workers. It has been reported that with constant high temperature (35 o C or more) treatment, either there is no nodulation 19 or the nodules are ineffective 20 . But, similar to our results, the diurnal cyclic temperature regimes like 41 o C for 6 or 9 h day -1 have shown to cause nodulation on the host plants by all the strains of bradyrhizobia 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Rhizobium sp. é afetado em temperaturas acima de 35 o C (HUNGRIA & FRANCO, 1993). Entretanto, durante o experimento, houve uma variação de temperatura entre 20,2 e 25,5 o C. Uma vez que o experimento foi irrigado sempre que necessário e o feijoeiro foi inoculado com estirpes de rizóbio tolerantes a altas temperaturas, é provável que os benefícios da cobertura morta na produção de grãos tenham decorrido, em grande parte, da proteção contra as larvas de C. arcuata.…”
Section: Resultsunclassified